Climate Gentrification: Methods, Gaps, and Framework for Future Research - Best, Kelsea; Jouzi, Zeynab (Frontiers in Climate, 2022)
The topic of climate gentrification has been receiving increasing attention in both peer-reviewed literature and in popular discourse. Climate gentrification refers to the ways that climate impacts and adaptations may contribute to changes in community characteristics and potential displacement of vulnerable residents through changes in property values. Here, we conduct a review of the current literature on climate gentrification in order to understand methods and key themes, identify research gaps, and guide future research. Our search yielded a total of 12 relevant articles, beginning in 2018. After reviewing these articles, we identified several key methodological gaps including the lack of participatory methods, limited availability of longitudinal data, difficulty defining and measuring displacement, and challenges surrounding causality. We suggest that future work on climate gentrification should draw from Coupled Human and Natural Systems (CHANS) theory to further understand the complex feedbacks that exist in climate gentrification dynamics. To guide future research, we propose a framework as a CHAN that highlights the multi-spatial, multi-temporal, and multi-faceted dimensions of climate gentrification.